“A’quelle que passou por mim e não me viu”: authored by Carmen Santos in Jornal das Moças - de Carvalho Castro, Tatiana (Temporalidades, 2023)
Carmen Santos, Brazilian filmmaker, businesswoman and author. She built a trajectory of representations and struggle for Brazilian cinema. This work addresses the authorial role of Carmen Santos as a writer and producer of her own writing through the publication of her personal diary in the pages of the illustrated magazine aimed at female consumption Jornal das Moças. Carmen Santos contributed to the periodical in the first decades of the 1930s, a cut that matches her intense presence and circulation in the discussion of the still incipient Brazilian cinema. This work seeks to analyze the authorship of Carmen Santos, as a woman, in a society that sought to silence her, as it did with many women at the beginning of the history of Brazilian cinema.